ChemInform Abstract: Polyol Synthesis of Nanoparticles: Status and Options Regarding Metals, Oxides, Chalcogenides, and Non‐Metal Elements. Issue 40 (October 2015) - Dong, H.; Chen, Y.‐C.; Feldmann, C.
Abstract Review: [180 refs.